Using a pair of phased antennas to improve UHF reception transmission in tunnels. - Coraiola, Alessandro; Sturani, Bruno
UHF propagation inside tunnels improves considerably if a pair of phased antennas is used as a fixed antenna system, instead of a single antenna. In this article, we have analyzed the causes of signal deterioration in a tunnel due to slow fading and fast fading. We obtained simple relations for their calculation, which are valid for a rectangular tunnel. We then demonstrated that the pair of phased antennas can reduce fast fading. The measurements performed on pilot projects in actual tunnels confirmed that the pair of phased antennas is capable of reducing fast fading, which is usually the real limiting factor for transmission in tunnels.
Keywords: Land mobile radio propagation factors; Underground electromagnetic propagation; Tunnels; Antenna arrays; Phased arrays; Mobile communication